Decisiones financieras, competencia en el mercado y desempe\~no de las empresas: Evidencia emprica para Iberoamerica - Manuel Sanchez Valadez (Banco de México, 2013)
– Economic literature had shown the existence of the interrelationship between the financial decisions of the firms and their competitive decisions; either by convenience or by data availability, most of empiric papers addressed separately the influence of both kinds of decisions over firm performance. With it, this paper through a cross-section model, which uses information of around 3,900 enterprises in 14 Iberoamerican countries, explores jointly the possible effects of both kinds of decisions of the firms (financial and competitive) over their performance. The results suggest the existence of differences in the relationships between variables accordingly the market competition intensity. Also the results suggest that the financial decisions of the firms could be used as an additional tool of the competitive strategy of the firms.
Keywords: G32; L20; 330; indebtedness; trade credit; competition; firm performance